VERZIFIKACIJSKE RAZLIKE V POEZIJI JUŽNOSLOVANSKIH NARODOV NA ŠIRŠEM MEDNARODNEM OZADJU - Novak, Boris Ante (Philological Studies, 2019)
The comparative analysis of the versification of the poetry of South Slavs shows an interesting „diversification“: the accentual-syllabic principle prevailed in the Slovenian poetry at the end of the 18th century due to Alexandrine verses published by Janez Damascen Dev in three almanachs Pisanice which advocated the Enlightment reforms. In other South Slav languages this versification was embraced (too) late, only at the end of the 19th century, in the epoch of the emergence of the modern poetry when metrical principles already dissolved; therefore, the accentual-syllabic versification has never become a firm structure, it has been coexisting ever since with the traditional, weakened syllabic versification. The accentual-syllabic versification is a common denominator between two geographically most distanced Slav languages, Slovenian and Russian where this reform took place already at the beginning of the 18th century, equally in the framework of the Enlightment programme. The fact that the verse rhythm in the South Slav languages follows such different principles means that the versification does not depend on lingustic (primarily phonetic) laws only, but on cultural and historical dimensions as well.